Recent Facets of Consumer Behaviour: A Case of Rural Market - Shinde, Rajesh (Indian Journal of Marketing, 2007)
According to the census of 2001, India’s total population is 102crore of which 71.89crore was of rural India, constituting 70% of the total population. Inspite of this fact, marketers earlier concentrated on the urban markets and scheduled their strategy accordingly. As the competition increased in urban areas, and taking into account the increasing demand for FMCG’s in rural areas, the marketers expanded their business in rural areas. Perhaps it has become a policy for their survival. Marketers found different strategies to penetrate in the rural segment. The pioneer corporate was HLL.Various surveys reveal that average rural household spends almost 60% of their income on the food, which is reasonably a high amount. The demand for FMCG in that way was going rapidly high as compared to the urban market. The market for FMCG is estimated at around Rs. 50,000 crore.